Ithaca effect (The importance of the journey) - Abregú Jaucha, Washington Neuman (2020)
This essay wants to make us think that due to the haste and speed of our time, and influenced by the will to quickly achieve our goals, one loses oneself of priceless jewels, great gifts of life; that unfortunately due to the acceleration in which we find ourselves, we ignore them or simply do not see them, thus dismissing the secondary roads, the other roads, the alternative ones with their unexpected gifts and this being the spirit of our time; That is why I intend under the name of Ithaca effect to give an alternative and under the superb influence of poetics and with the epiphany of the homonymous poem Ithaca by Konstantinos Kavafis, to reflect on the value of the path in the future of our lives, and that in the end they would be those that would enrich our interiorities, that is to say our inner cities or contents and above all learning not to give an exaggerated importance to the goals, in favor of alternative paths and their pleasant surprises, which fortunately of serendipities (unplanned lucky encounters) They can make us better people, of course if we are willing to travel these other paths, the best ones, the ones that magnify our goals.